ChemInform Abstract: Sunlight‐Driven Copper‐Catalyst Activation Applied to Photolatent Click Chemistry. Issue 12 (March 2015) - Beniazza, Redouane; Lambert, Romain; Harmand, Lydie; Molton, Florian; Duboc, Carole; Denisov, Sergey; Jonusauskas, Gedeminas; McClenaghan, Nathan D.; Lastecoueres, Dominique; Vincent, Jean‐Marc
Abstract The copper‐catalyst CUA can be activated by irradiation with daylight or light of 365 nm.